Living and dying well in Philippians a comparative analysis of ancient sources - Lamb, Gregory E. 1972-; Mohr Siebeck GmbH & Co. KG (Tübingen Mohr Siebeck, 2025)
Cover -- Title -- Acknowledgements -- Table of Contents -- List of Abbreviations -- Chapter 1: Human Flourishing as a Subject of Pauline Research -- A. Kaleidoscopic Scope and Relevance for Biblical Studies -- I. Thesis, Scope, and Purpose -- 1. Thesis -- 2. Scope -- 3. Purpose -- II. Why Study Paul's Conception of Living and Dying Wellin Philippians? -- B. Review of Literature -- I. Monographs -- 1. John Behr, The Mystery of Christ (2006) -- 2. John M. Frame, The Doctrine of the Christian Life (2008) -- 3. John Swinton and Richard Payne, Living Well and Dying Faithfully (2009) -- 4. Michael J. Gorman, Becoming the Gospel (2015) -- 5. Alexander N. Kirk, The Departure of an Apostle (2015) -- 6. Scot McKnight and Joseph B. Modica, eds., The Apostle Paul and the Christian Life (2016) -- II. Articles -- 1. James L. Jaquette, "Life and Death, Adiaphora, and Paul's Rhetorical Strategies" (1996) -- 2. Rollin A. Ramsaran, "Living and Dying, Living Is Dying (Philippians 1:21)" (2002) -- 3. Nijay K. Gupta, "'I Will Not Be Put to Shame'" (2008) -- 4. Jeremy Punt, "A Biblical Death-Wish" (2009) -- III. Dissertations -- 1. James P. Ware, "'Holding Forth the Word of Life'" (1996) -- 2. Audrey Lynn Sharon West, "Whether by Life or by Death" (2001) -- C. Lacunae within the Current State of Research -- D. Overview of the Study -- Chapter 2: Comparative Methodology -- A. Comparative Analysis and Philippians -- I. Comparative Analysis: Toward an Understanding -- II. Comparative Analysis: A Viable Methodology to Study Paul and Philippians? -- B. Criteria for the Selection of Sources -- Chapter 3: Living and Dying Well in Philippians -- A. Flourishing as a Foundational Subtext -- B. Exegetical Analysis -- I. Paul's Argumentatio: Propositio (Phil 1:27-30) -- 1. Philippians 1:27 -- 2. Philippians 1:28 -- II. Paul's Argumentatio: Probatio (Phil 2:1-30).
Description based on publisher supplied metadata and other sources
Keywords: Hochschulschrift